Exploring the signalling potential of mega-sporting events : an analysis of the 2010 FIFA World Cup in South Africa - Jenkins, David (School of Management Studies, 2016)
Mega-sporting events such as the 2008 Olympic Games in Beijing, the 2010 FIFA World Cup in South Africa and the 2014 FIFA World Cup in Brazil have been observed to serve as highly influential tools for the promotion of positive media impressions surrounding the host destination. Drawing from the field of existing knowledge surrounding the sociology of sport, the media and media content analysis, this study reports on a media content analysis conducted on the local news coverage of the 2010 FIFA World Cup in selected South African newspapers. Monitoring coverage over and eight-year pre- and post-event period, the analysis identified five principal themes: stadiums; safety and security; Bafana-Bafana; social-impact; and economic-impact. The findings indicated a cyclical-type shift in conversation, where focus was placed on impressions of host-nation capabilities and readiness in the lead up to the event, to profound euphoria, unity and pride during the hosting stages of the event, and finally onto critical impact and legacy evaluation in the post-event phase. The sentiment of the coverage was largely balanced across all periods, with the total number of positive references only slightly exceeding that of negative references. These findings serve as critical insight to the work of event organisers, media managers and policy developers alike, whom all hold a vested interest in managing the perceived impressions of mega-sporting events. Practical implications for these stakeholders include: i) establishing greater clarity with respect to the overall signalling benefits of mega-sporting; and ii) informing media management campaigns to reinforce the power of mega-sporting events as a positive reference point - especially in the post-event legacy period.